A review of wound healing activity on different wound models - Verma, Renuka; Gupta, Pushpa Prasad; Satapathy, Trilochan; Roy, Amit (Journal of Applied Pharmaceutical Research, 2019)
Wound is an injury of living tissue or break in the epithelial integrity of the upper layer of skin.which may lead to disturbance of skin anatomical structure and their function. The normal wounds are starts to healing immediately after an injury. Healing process are involved a series of coordinated events (inflammatory response, proliferation, maturation phase).  Wound healing remains a challenging clinical problem therefore correct and efficient wound management is essential. The screening models are important biological tools to understand basic process of tissue repair and treatment of wounds. Wide varieties of in-vitro, ex-vivo and in-vivo models have been developed for evaluation of wound healing activity. The in-vitro models includes Chick chorioallantoic membrane assay, Fibroblast assay, Collagen assay, Scratch assay, Endothelial cell in vitro tube formation assay, Keratinocytes assay. ex-vivo models includes organotypic culture, human ex vivo skin culture, porcine model, Human organotypic skin explanted culture And the  in-vivo models includes Excision wound model, Incision wound Model, Burn wound model, Dead space wound model, Skin wound induction.the aim of this review is detailed study on different types of in-vitro, ex-vivo and in-vivo models for evaluation of wound healing activity.